The Implementation of an Integrated Learning Management System: Challenges in the Indonesian Bureaucratic Organizational Structure - Samsara, Ladiatno; Cahyarini, Benedicta Retna; Kusuma, Harditya Bayu (KnE Social Sciences, 2022)
The rapid changes in technology have impacted civil servant competency development, from training to learning aspects. From the learning perspective, public sector employees can measure their skills and abilities (self-assessment) to make sure that competency development is carried out according to their needs. An integrated learning management system (integrated LMS) can help support this competency development of government employees. However, integrated LMS development faces challenges related to the public sector organizational structure that is built uniformly using Mintzberg’s approach. In fact, each government institution has its unique needs in terms of organizational structure. Therefore, this paper analyzed the challenges in implementing an integrated LMS, employing Mintzberg’s organization framework. A literature search was conducted of books, news articles, academic literature and reports to evaluate the impact of integrated LMS implementation on the effectiveness of bureaucracy organizational structure and civil servant competency development. In conclusion, the article showed that the organizational structure of the Indonesian bureaucracy is treated and built similarly in every level and sector which leads to overlapping authority, programs and activities, and results in obstacles in the implementation of an integrated LMS. Keywords: integrated LMS, organizational structure, competency development